A general evidence-based sequence variant control limit for recombinant therapeutic protein development. Issue 1 (1st January 2020) - Zhang, Aming; Chen, Zhengwei; Li, Meinuo; Qiu, Haibo; Lawrence, Shawn; Bak, Hanne; Li, Ning
ABSTRACT: Sequence variants (SVs) resulting from unintended amino acid substitutions in recombinant therapeutic proteins have increasingly gained attention from both regulatory agencies and the biopharmaceutical industry given their potential impact on efficacy and safety. With well-optimized production systems, such sequence variants usually exist at very low levels in the final protein products due to the high fidelity of DNA replication and protein biosynthesis process in mammalian expression systems such as Chinese hamster ovary cell lines. However, their levels can be significantly elevated in cases where the selected production cell line has unexpected DNA mutations or the manufacturing process is not fully optimized, for example, if depletion of certain amino acids occurs in the cell culture media in bioreactors. Therefore, it is important to design and implement an effective monitoring and control strategy to prevent or minimize the possible risks of SVs during the early stage of product and process development. However, there is no well-established guidance from the regulatory agencies or consensus across the industry to assess and manage SV risks. A question frequently asked is: What levels of SVs can be considered acceptable during product and process development, but also have no negative effects on drug safety and efficacy in patients? To address this critical question, we have taken a holistic approach and conducted a comprehensive sequence variant analysis. To guide biologic development, a general SV control limit of 0.1% at individual amino acid sites was proposed and properly justified based on extensive literature review, SV benchmark survey of approved therapeutic proteins, and accumulated experience on SV control practice at Regeneron.